A multi-criteria decision-making (MCDM) model in the security forces operations based on rough sets - Karavidić, Zoran; Projović, Damir (Decision Making: Applications in Management and Engineering, 2018)
The paper points to a multi-criteria decision-making model based on the rough set theory application. The model demonstrates exceptional importance of the software application of the rough sets to decision-making in the security forces operations. Applying the rough sets represents a useful tool when the data, needed for the decision-making process, include vagueness and uncertainty. By applying the model based on the applicative use of the rough sets, specific decision-making rules are formulated. These rules guide the decision-makers through the complete process of planning the security operations